2017
DOI: 10.1177/1060028017698797
|View full text |Cite
|
Sign up to set email alerts
|

Impact of A Collaborative Strategy to Reduce the Inappropriate Use of Acid Suppressive Therapy in Non–Intensive Care Unit Patients

Abstract: A collaboration between clinical pharmacists and a hospitalist service can significantly reduce the inappropriate use of AST in non-ICU patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(27 citation statements)
references
References 25 publications
0
26
0
1
Order By: Relevance
“…The PRISMA flowchart of study inclusion is illustrated in Fig 1 [55]. After screening and determination of eligibility of 14,422 citations, 17 articles published between 2007 and 2019 were ultimately included in the meta-analysis [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]. These 17 publications resulted in 16 studies since Buckley et al [65] reported data for both the ICU and non-ICU settings in a single publication and two authors published results of pre-and post-intervention data in separate articles; in the ICU setting: Wohlt et al (pre-implementation) [75] and Hatch et al (post-implementation) [68]; in the non-ICU setting: Khudair et al (pre-implementation) [71] and Khudair et al (post-implementation) [70].…”
Section: Study Inclusionmentioning
confidence: 99%
“…The PRISMA flowchart of study inclusion is illustrated in Fig 1 [55]. After screening and determination of eligibility of 14,422 citations, 17 articles published between 2007 and 2019 were ultimately included in the meta-analysis [63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79]. These 17 publications resulted in 16 studies since Buckley et al [65] reported data for both the ICU and non-ICU settings in a single publication and two authors published results of pre-and post-intervention data in separate articles; in the ICU setting: Wohlt et al (pre-implementation) [75] and Hatch et al (post-implementation) [68]; in the non-ICU setting: Khudair et al (pre-implementation) [71] and Khudair et al (post-implementation) [70].…”
Section: Study Inclusionmentioning
confidence: 99%
“…Twenty studies evaluated targeted drug programs (Table S3). The majority of these evaluations utilized study designs at high risk of bias. Nonrandomized posttest designs with a historical control comprised 55% studies, followed by single‐group posttest (15%), single‐group pretest‐posttest (10%), and nonrandomized pretest‐posttest with a historical control (5%).…”
Section: Resultsmentioning
confidence: 99%
“…Antimicrobial cost per patient day was reported to be lower with pharmacist stewardship, which ranged from $3.09 to $64.13 . Other targeted drug programs evaluated stewardship of other drug types such as erythropoietin and acid suppression . These studies reported cost savings, which ranged between $37000 and $198352 annually.…”
Section: Resultsmentioning
confidence: 99%
“…( 2 , 7 ) However, in spite of reduced major bleeding with acid suppressants, little or no effect of acid suppressive therapy was noted on mortality and patients in non-intensive care unit. ( 8 , 9 ) As much as pharmacologic therapy with anti-secretary drugs, enhanced gastric defense system can be alternate or combinational enhancer to cover the limitation of acid suppressive therapy since pre-epithelial factors, an epithelial barrier, and subepithelial factors are also principally implicated in SRMD. ( 10 )…”
Section: Introductionmentioning
confidence: 99%